2016
DOI: 10.1016/j.athoracsur.2016.01.063
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram to Predict Recurrence and Survival of High-Risk Patients Undergoing Sublobar Resection for Lung Cancer: An Analysis of a Multicenter Prospective Study (ACOSOG Z4032)

Abstract: Background Individualized prediction of outcomes may help with therapy decisions for patients with non-small cell lung cancer (NSCLC). We developed a nomogram by analyzing 17 clinical factors and outcomes from a randomized study of sublobar resection for NSCLC in high-risk operable patients. The study compared sublobar resection alone, to sublobar resection with brachytherapy. There were no differences in primary and secondary outcomes between the study arms, and were thus combined for this analysis. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Tsutani et al 3 found no statistically significant difference in overall survival (OS) or recurrence-free survival between patients treated by segmentectomy versus wedge resection for ground glass opacity (GGO)-dominant clinical stage Ia NSCLC. Similar results have been reported by Fiorelli et al, Hamatake et al, and Kent et al [4][5][6] Hou et al 7 conducted a meta-analysis of nine studies and found no significant difference in disease-free survival (DFS) of patients with stage I NSCLC receiving segmentectomy versus wedge resection. Some previous metaanalyses that have compared the clinical outcomes of lobectomy, segmentectomy, and wedge resection in patients with stage I NSCLC categorized segmentectomy and wedge resection together as "sublobar resection."…”
Section: Introductionsupporting
confidence: 80%
“…Tsutani et al 3 found no statistically significant difference in overall survival (OS) or recurrence-free survival between patients treated by segmentectomy versus wedge resection for ground glass opacity (GGO)-dominant clinical stage Ia NSCLC. Similar results have been reported by Fiorelli et al, Hamatake et al, and Kent et al [4][5][6] Hou et al 7 conducted a meta-analysis of nine studies and found no significant difference in disease-free survival (DFS) of patients with stage I NSCLC receiving segmentectomy versus wedge resection. Some previous metaanalyses that have compared the clinical outcomes of lobectomy, segmentectomy, and wedge resection in patients with stage I NSCLC categorized segmentectomy and wedge resection together as "sublobar resection."…”
Section: Introductionsupporting
confidence: 80%
“…A tremendously high proportion of patients, 40% to 70%, have not even one single LN removed or examined (35)(36)(37), and this proportion is worse following wedge resection when compared to segmentectomy (36). Even in the frame of the randomized ACOSOG Z4032 trial designed to specifically evaluate surgical outcomes, and comparing sublobar resection alone with sublobar resection with brachytherapy in patients with clinical stage I non-small lung cancer, more than one third of the patients did not receive any kind of LN evaluation (38). With this background, the incidence of regional recurrence after stereotactic body radiation therapy (SBRT) or surgery is intuitively expected to be comparable, as shown by the available evidence (39).…”
Section: Is Systematic Lymphadenectomy Beneficial In Clinical N0 Disementioning
confidence: 99%
“…7 Sentinel lymph node mapping is particularly advantageous in the era of lung cancer screening during which small and semisolid nodules are subject to limited resection for diagnosis and therapy but still require accurate nodal staging. In addition, a limited nodal dissection facilitated by SLN mapping permits subsequent nodal staging if a second primary tumor occurs.…”
Section: How Will This Affect Clinical Care?mentioning
confidence: 99%